1995
DOI: 10.1002/cne.903590406
|View full text |Cite
|
Sign up to set email alerts
|

NGF‐dependent and NGF‐independent recovery of sympathetic function after chemical sympathectomy with 6‐hydroxydopamine

Abstract: To help clarify the distinction between the nerve growth factor (NGF)-dependent collateral sprouting of sympathetic nerves and their NGF-independent regeneration after crush, we used 6-hydroxydopamine (OHDA) to destroy the sympathetic terminals in adult rats; this leaves the axons damage-free. Would recovery occur by regeneration and/or collateral sprouting? A single 6-OHDA injection abolished the sympathetic pilomotor field revealed by electrical stimulation of a cutaneous nerve. Recovery began within 2 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…For example, following transection of the sciatic nerve it has been shown that the neurotrophin receptor p75 and the neurotrophin nerve growth factor (NGF) are up-regulated by non-neuronal cells, and it was originally proposed that NGF binding to these receptors played an important role in sensory and sympathetic nerve regeneration (Taniuchi et al, 1986; Heumann et al, 1987; Taniuchi et al, 1988). However, evidence from Diamond and colleagues and others demonstrated that sensory and sympathetic regeneration is not affected by blockade of endogenous NGF, although under the same conditions collateral sprouting is blocked (Rich et al, 1984; Diamond et al, 1987, 1992; Gloster and Diamond, 1992, 1995; Doubleday and Robinson, 1995). …”
Section: Responses Of the Distal Nerve And The Axotomized Cell Body Amentioning
confidence: 99%
“…For example, following transection of the sciatic nerve it has been shown that the neurotrophin receptor p75 and the neurotrophin nerve growth factor (NGF) are up-regulated by non-neuronal cells, and it was originally proposed that NGF binding to these receptors played an important role in sensory and sympathetic nerve regeneration (Taniuchi et al, 1986; Heumann et al, 1987; Taniuchi et al, 1988). However, evidence from Diamond and colleagues and others demonstrated that sensory and sympathetic regeneration is not affected by blockade of endogenous NGF, although under the same conditions collateral sprouting is blocked (Rich et al, 1984; Diamond et al, 1987, 1992; Gloster and Diamond, 1992, 1995; Doubleday and Robinson, 1995). …”
Section: Responses Of the Distal Nerve And The Axotomized Cell Body Amentioning
confidence: 99%
“…Collateral sprouting is from undamaged, intact axons of neighbouring regions while regenerative sprouting is from damaged axons of the injured nerve. Additionally, collateral sprouting was found to be dependent on growth factors derived from the target tissue, namely NGF, while regenerative sprouting was NGF-independent (Gloster and Diamond, 1995;Ro et al, 1998). The source of sympathetic sprouting into the upper dermis in this model is unknown as sympathetic fibres in the rat hindlimb travel in both the sciatic nerve as well as along blood vessels.…”
Section: Source Of Sympathetic and Sensory Sproutingmentioning
confidence: 99%
“…This peptide is not only an important component of wound healing and tissue repair [31] but also an inductor of sprouting of sensory afferent nerve fibers [9,54]. Diamond and his group [13,14,22,23] stated that NGF mediates collateral sprouting in rats, but that regenerative sprouting is NGF independent. In fact, the sprouting of cutaneous nerves and an increase of NGF at the same time has been shown by Leslie et al [41] in inflamed rat paws.…”
Section: Innervation Of the Spinal Dura Mater Lumbalismentioning
confidence: 99%